Human activities affecting lesser flamingo (Phoeniconaias minor) habitat in Momella lakes, Tanzania - Deogratias Ladislaus Lihepanyama; Patrick Alois Ndakidemi; Janeth Jonathan Marwa; Anna Christina Treydte (Journal of Land Use Science)
Land use/land cover (LULC) change, caused by human activities, can strongly affect wildlife species and their habitats. Yet, human impacts onto lakes and associated indicator bird species such as the lesser flamingos (Phoeniconaias minor) have rarely been investigated. We used remote sensing images from 1989 to 2019, with additional interviews and focus group discussions to investigate how LULC change and agricultural activities adjacent to the Momella lakes, Tanzania, have affected the flamingo habitat. Agricultural areas increased strongly over time, and most respondents earned their living through crop farming. The use of synthetic fertilizers, and limited knowledge about fertilizer effects on environmental health, were evident. We highlight that LULC data combined with socio-economic assessments is essential to understanding the dynamics and impacts of human activities on wildlife. We recommend training for sustainable farming practices around areas of high conservation values and integrating land use changes and socio-economic dynamics into conservation efforts.